Religiousness and Cultural Competences among Nurses in the Context of Social Changes - Jadwiga Małgorzata Bąk; Barbara Niedorys; Agnieszka Chrzan-Rodak; Krzysztof Jurek; Danuta Zarzycka; Barbara Ślusarka (Rozprawy Społeczne)
Abstract The main objective is to search for a correlations between spiritual traits of nurses and cultural competences